Vibrational Circular Dichroism Unravels Supramolecular Chirality and Hydration Polymorphism of Nucleoside Crystals - Krupová, Monika; Leszczenko, Patrycja; Sierka, Ewa; Emma Hamplová, Sára; Pelc, Radek; Andrushchenko, Valery (Chemistry (Weinheim an der Bergstrasse, Germany), 2022)
Vibrational circular dichroism (VCD) spectroscopy has been widely used to study (bio)molecules in solution. However, its solid-state applications have been restricted due to experimental limitations and artifacts. Having overcome some of them, the first VCD study of nucleoside crystals is now presented. A two-orders-of-magnitude enhancement of VCD signal was observed due to high molecular order in the crystals and resulting supramolecular chirality. This allowed to obtain high-quality VCD spectra within minutes using minute amounts of samples. The VCD technique is extremely sensitive in detecting changes in a crystal order and is able to distinguish different hydration states of crystals. This elevates it to a new level, as a fast and efficient tool to study chiral crystalline samples. This study demonstrates that VCD is capable of near-instantaneous detection of hydration polymorphs and crystal degradation, which is of substantial interest in pharmaceutical industry (quality and stability control).
Keywords: chirality; solvomorphism; enhanced VCD; nukleosidy; stereoizomerie; crystal engineering; solid-state VCD; Nucleosides; Stereoisomerism; cirkulární dichroismus; Circular Dichroism